2018
DOI: 10.1007/s12671-017-0856-1
|View full text |Cite
|
Sign up to set email alerts
|

A Randomised Controlled Trial of a Brief Online Mindfulness-Based Intervention in a Non-clinical Population: Replication and Extension

Abstract: Building on previous research, this study compared the effects of two brief, online mindfulness-based interventions (MBIs; with and without formal meditation practice) and a no intervention control group in a non-clinical sample. One hundred and fifty-five university staff and students were randomly allocated to a 2-week, self-guided, online MBI with or without mindfulness meditation practice, or a wait list control. Measures of mindfulness, perceived stress, perseverative thinking and anxiety/depression sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
91
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(112 citation statements)
references
References 77 publications
15
91
0
6
Order By: Relevance
“…Another study found conflicting results and demonstrated improvements on psychological symptoms for both intervention arms (informal practice only and seated meditation) compared to a waitlist control (Cavanagh et al, 2018). In HCPS, one study found an informal mindfulness exercise to improve state-level stress following difficult patient encounters relative a usual care group in family medicine residents (Edgoose, Regner, & Zakletskaia, 2015).…”
Section: Aim 5 Crossover Design and Investigation Of Mediatorsmentioning
confidence: 99%
“…Another study found conflicting results and demonstrated improvements on psychological symptoms for both intervention arms (informal practice only and seated meditation) compared to a waitlist control (Cavanagh et al, 2018). In HCPS, one study found an informal mindfulness exercise to improve state-level stress following difficult patient encounters relative a usual care group in family medicine residents (Edgoose, Regner, & Zakletskaia, 2015).…”
Section: Aim 5 Crossover Design and Investigation Of Mediatorsmentioning
confidence: 99%
“…For longitudinal targets, we modelled three commonly-cited MT benefits: improved subjective wellbeing, attentional control [8][9][10][11]13], and interoceptive integration [31][32][33][34]. For local targets, we tested for improvements in mood, physiological arousal [24,35,36], and stress [11,22,26,37].…”
Section: Goal and Hypothesesmentioning
confidence: 99%
“…Moreover, a systematic review found no relationship between hours spent in MT sessions and changes in psychological distress [25], suggesting that formal meditation time is not the most important factor in efficacious MT. Indeed, a recent dismantling study of internet-based MT found no effect of formal meditation practice, although both formal and non-formal practice arms of the study outperformed a no-intervention control group [26].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies43 60–63 and meta-analyses64 65 found evidence for the efficacy of online mindfulness-based interventions with the focus on self-reported health variables (eg, depression, anxiety, and stress). For example, Spijkerman et al 64 compared 15 randomised control trials and showed small to medium effect sizes regarding the reduction of anxiety (g=0.22; 95% CI: 0.05 to 0.39), improvement of depression (g=0.29; 95% CI: 0.13 to 0.46), well-being (g=0.23; 95% CI: 0.09 to 0.38), and mindfulness (g=0.32; 95% CI: 0.23 to 0.42) in healthy samples as well as samples with mental disorders.…”
Section: Introductionmentioning
confidence: 99%